Sialidase assay and analysis of free sialic acid in tsetse (Glossina sp.) collected in protected and tsetse invested areas in Nigeria - Judith Sophie Weber; Stephen Saikiu Shaida; Sen Claudine Henriette Ngomtcho; Usman Baba Musa; Ahmadu Adamu; Thaddeus Terlumun Gbem; Petra Berger; Mohammed Mamman; Jonathan Andrew Nok; Sørge Kelm (PANGAEA, 2020)
This data set includes results of a sialidase assay applied in tsetse gut tissue from a tsetse (Glossina sp.) collection carried out in Nigeria between 2014 and 2016. Traps were employed for one to three days in four different National Parks, one Game Reserve and two tsetse invested areas. Each tsetse was identified morphologically and dissected in the field, all tissues preserved and used for further analysis. The whole gut of each tsetse was homogenized in the field and partially preserved for DNA analysis and used to investigate for sialidase activity with a fluorescent substrate and a natural substrate. Analysis for sialidase activity was done by fluorescent measurement and reverse phase HPLC of processed gut samples.
In: Weber, JS et al. (2020): Molecular and morphological characterization of Glossina sp. and identification of associated Trypanosoma sp. in Nigeria including analysis for sialidase activity [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.915145